Pengembangan Media Pembelajaran Menulis Puisi dalam Bentuk Audia Visual Berbasis Pendidikan Karakter Siswa Kelas X SMA Al-Hikmah Medan - Muhammad Fahreza; Rita; Nila Safina (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2022)
This study aimed to describe the development process and fasibility of new poetry writing learning media in the form of audio-visual-based character education for class X SMA Al-Hikmah Medan. The source of data in this study is a questionmaire. The data collection techniques are observation and interviews to gain data in learning to write new poetry based on character education. This study used the research and development (R&D) by Borg and Gall that consists of 7 stages; 1)needs analysis, 2)product development, 3)expert validation, 4)first stage revision, 5)field trial, 6)second stage revision and, 7)final product. The researchers tested the product in large and small groups. The material expert validation of the newly developed poetry writing learning media obtained and overall average as 82% or “Very Satisfacation”means that it deserves to be tested into large and small groups. The media experts obtained and overall average as 94% or “Very Satisfacation” means that it deserves to be tested into large and small groups. The results of small group test got 99% and the large group got 97%. Based on the percetages obtained for the developed learning media, the learning media is declared to be effectively used in learning in class X.